Pengaruh e-Sistem Pajak, Kualitas Pelayanan Pajak, dan Kesadaran WPOP terhadap Kepatuhan WPOP - Julianti, Erna; Yantiana, Nella; Damayanti, Fera; Ardhi, Qisthi (Jurusan Akuntansi Politeknik Negeri Pontianak, 2024)
This research aims to test and analyze the influence of e-tax systems, tax service quality, and taxpayer awareness on the compliance of individual taxpayers at the East Pontianak Primary Tax Office (KPP Pratama Pontianak Timur). The research was conducted using a quantitative descriptive method. This study was carried out by examining data from 108 respondents who filled out questionnaires at the East Pontianak Primary Tax Office. Data analysis was conducted using validity and reliability tests, classic assumption tests, multiple linear regression, hypothesis testing through t-tests and F-tests, as well as coefficient of determination tests. The results of the research show that e-tax systems, tax service quality, and taxpayer awareness simultaneously have a significant effect on the compliance of individual taxpayers in paying taxes, with the magnitude of the influence being 41.4%. Furthermore, partially, the e-tax system variable does not have a significant effect on the compliance of individual taxpayers in paying taxes. Meanwhile, tax service quality has a significant positive effect on the compliance of individual taxpayers in paying taxes. Taxpayer awareness has a significant positive effect on the compliance of individual taxpayers in paying taxes.